Developing Research-Based Instructional Materials to Support Large-Scale Transformation of Science Teaching and Learning: The Approach of the OpenSciEd Middle School Program. Issue 7 (3rd October 2021) - Edelson, Daniel C.; Reiser, Brian J.; McNeill, Katherine L.; Mohan, Audrey; Novak, Michael; Mohan, Lindsey; Affolter, Renee; McGill, Tara A. W.; Buck Bracey, Zoë E.; Deutch Noll, Jamie; Kowalski, Susan M.; Novak, Dawn; et al.
ABSTRACT: OpenSciEd is an ambitious effort to implement the vision of the Framework for K-12 Science Education and the Next Generation Science Standards broadly across the United States. The premise of OpenSciEd is that high quality instructional materials can play a critical role in transforming science teaching and learning at a broad scale. To achieve its goal, this collaborative project is developing instructional materials for middle school science that support the shifts in practice required to achieve the outcomes called for by the Framework for K-12 Science Education and the Next Generation Science Standards at a large scale. The OpenSciEd Middle School Program development project is addressing the challenge of making large changes in practice at a large scale through attention to (1) who participates in design and development, and how; (2) providing explicit guidance for developers in a comprehensive design framework; and (3) a design and development process that ensures participation from the desired participants and adherence to the guidelines of the design framework. The resulting instructional materials have shown promise in external reviews and field tests, but their success in achieving the project's goals for transforming science will depend on the circumstances in which the program is implemented.